Acute Clinical Features and Persistence of Joint Pain in Probable Cases of Chikungunya Fever in Eritrea - Frezgi O; Berhane A; Ghebrewelde G; Tekie H; Kiflezgi T; Mohamedsied A; Tekie Y; Asrat MM; Gebrejesus T (Open Access Rheumatology: Research and Reviews)
Okbu Frezgi,1,2 Araia Berhane,3 Ghide Ghebrewelde,4 Henok Tekie,4 Tsegezab Kiflezgi,4 Abdelaziz Mohamedsied,4 Yonas Tekie,4 Medhanie Medhin Asrat,5 Tewaldemedhine Gebrejesus6 1Orotta National Referral Maternity Hospital, Ministry of Health, Asmara, Eritrea; 2Gynecology and Obstetrics Department, Orotta College of Medicine and Health Sciences, Asmara, Eritrea; 3Communicable Disease Control program, Ministry of Health, Asmara, Eritrea; 4Tesseney Hospital, Ministry of Health, Tesseney, Eritrea; 5Statistical Data Processing, Eritrean national Statistics office, Asmara, Eritrea; 6National Tuberculosis and Leprosy Control Program of Eritrea Ministry of Health, Virginia, USACorrespondence: Okbu Frezgi, Email lurgewra@gmail.comBackground: Chikungunya fever is a mosquito-borne viral illness that has re-emerged as an important global concern. Persistent arthralgia following chikungunya fever is common and requires advanced pharmacological interventions as pain does not respond well to analgesics.Objective: The study aimed to describe the acute clinical features of probable cases of chikungunya fever and risk factors associated with the persistence of joint pain.Methods: A prospective, descriptive cohort study was conducted on probable cases of chikungunya fever from October 2018 to March 2019 in the Tesseney subzone of Eritrea.Results: A total of 203 probable cases of chikungunya fever were enrolled, majority being males (68%) with a mean age of 39.2 years. The acute phase symptoms include the triad of polyarthralgia (97%), fever (96.1%), and skin rash (56.7%). Commonly affected joint sites were the wrist (59.4%) and interphalangeal joints of the hands (56.9%). Fever had a mean duration of 4.1 ± 3 days, while headache had a mean duration of 3.8 ± 3 days. Skin rash was maculopapular, which was pruritic in (85.2%) and the common involved sites were the hands (71%) and trunk (46.5%). Complete blood count during acute phase includes lymphocytosis (64.5%) and granulocytopenia (43.3%). Joint pain persisted at three months in 52.1% of cases and at six months in 21.7%. Age > 41 (p = 0.001, OR: 1.588; 95% CI: 0.935– 2.695) and having the O-type blood group (p = 0.033, OR: 0.704; 95% CI: 0.448– 1.105) were found to be associated with the persistence of joint pain.Conclusion: Our study indicates polyarthralgia, fever, and skin rash as a triad of symptoms during the acute phase. Persistent arthralgia was a frequent long-term complication of chikungunya fever in which increasing age was identified to be a significant risk factor.Keywords: chikungunya fever, clinical features, persistent joint pain, Eritrea